OXYGEN ISOTOPE EVIDENCE FOR SUBDUCTION AND RIFT-RELATED MANTLE METASOMATISM BENEATH THE COLORADO PLATEAU-RIO GRANDE RIFT TRANSITION - Perkins G.B.; Sharp Z.D.; Selverstone J. (My University, 2006)
Spinel lherzolite and pyroxenite xenoliths from the Rio Puerco Volcanic Field, New Mexico, were analyzed for oxygen isotope ratios by laser fluorination. In lherzolites, olivine δ18O values are high (+5.5‰), whereas δ18O values for pyroxenes are low (cpx=+5.1‰ opx=+5.4‰) compared to average mantle values. Pyroxenite δ18O values (cpx=+5.0‰ opx=+5.3‰) are similar to those of the lherzolites and are also lower than typical mantle oxygen isotope compositions. Texturally and chemically primary calcite in pyroxenite xenoliths is far from isotopic equilibrium with other phases, with δ18O values of +21‰. The isotopic characteristics of the pyroxenite xenoliths are consistent with a petrogenetic origin from mixing of lherzolitic mantle with slab-derived silicate and carbonatite melts. The anomalously low δ18O in the pyroxenes reflects metasomatism by a silicate melt from subducted altered oceanic crust, and high δ18O calcite is interpreted to have crystallized from a high δ18O carbonatitic melt derived from subducted ophicarbonate. Similar isotopic signatures of metasomatism are seen throughout the Rio Puerco xenolith suite and at Kilbourne Hole in the southern Rio Grande rift. The discrete metasomatic components likely originated from the subducted Farallon slab but were not mobilized until heating associated with Rio Grande rifting occurred. Oxygen diffusion modeling requires that metasomatism leading to the isotopic disequilibrium between calcite and pyroxene in the pyroxenites occurred immediately prior to entrainment. Melt infiltration into spinel-facies mantle (xenoliths) prior to eruption was thus likely connected to garnet-facies melting that resulted in eruption of the host alkali basalt. © Springer-Verlag 2006.